Development of a Full-Scale Structural Testing Program to Evaluate the Resistance of Australian Houses to Wind Loads - Boughton, Geoffrey Neville; Parackal, Korah; Satheeskumar, Navaratnam; Henderson, David James (Frontiers in Built Environment, 2017)
Extensive damage to houses during severe tropical cyclones in the 1970s in Australia highlighted the need for research-based structural engineering principles to be applied in design and construction of houses. Houses have structural redundancies and complex load paths, so the analysis of even simple houses was complicated. In order to evaluate the structural performance of these parallel systems, full-scale house testing commenced at the Cyclone Testing Station (CTS) in the early 1980s with the static multipoint loading of an old house destined for demolition. Following that test program, nine full-scale houses were tested under static and cyclic loading to evaluate load paths in different types of houses with different building practices and materials. Results have been incorporated into amendments of house construction codes, standards and manuals. Advances in computer modeling and instrumentation have led to more sophisticated full-scale studies. Data on real houses under construction has informed this work and enabled analytical models to incorporate variability in strength of connections in a way that a single test cannot. Progressive failure in the structural systems of timber-framed housing can now be studied to differentiate between houses that have significant damage and seemingly identical ones that have limited damage in the same wind event. These studies involve wind tunnel investigations to determine temporal pressure distributions; full-scale multiple tests on connections (with and without construction defects) to determine statistical distributions of strength and load/deflection relationships; and full-scale tests on houses or portions of houses to determine load sharing mechanisms between parallel structural and non-structural elements. The results of the test programs were used to calibrate the analytical models, which can be used for reliability studies. The paper presents a summary of the methodology and findings from previous CTS full-scale house tests. The results of the most recent research using full-scale tests on a portion of a house and its companion numerical models are discussed and the benefits and limitations of the process outlined.